Ceramide mediates lung fibrosis in cystic fibrosis - Ziobro, Regan (2013)
Fibrosis of the lung is one of the major clinical problems of cystic fibrosis and chronic obstructive pulmonary disease. However, the molecular mechanisms leading to pulmonary fibrosis are poorly characterized and require definition. Here, we demonstrate that chronic accumulation of ceramide in the lung contributes to the development of fibrosis in aged cystic fibrosis mice. Genetic or pharmacological normalization of ceramide in cystic fibrosis mice, which was achieved by heterozygosity of acid sphingomyelinase or chronic (6.5 month long) treatment of mice with pharmacological inhibitors of acid sphingomyelinase significantly decreased the development of lung fibrosis. Moreover, our studies demonstrate that long-term treatment of cystic fibrosis mice with pharmacological inhibitors of acid sphingomyelinase or genetic heterozygosity of the enzyme also minimizes pulmonary inflammatory cytokines in cystic fibrosis mice. This data identifies ceramide as a key molecule associated with pulmonary fibrosis in cystic fibrosis mice and demonstrate for the first time that prolonged inhibition of acid sphingomyelinase is able to attenuate fibrosis and inflammation in this animal model.